Determinats of Profitability and Implications on Corporate Value - Anik Agustina ZM (Journal of Accounting and Finance Management, 2021)
This study aims to prove empirically the determinants of profitability and their implications for firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2015-2019 period by using a panel data regression model with 25 manufacturing companies as the research sample. Based on the empirical results, the influencing variables positive and significant impact on profitability is Managerial Share Ownership, Audit Committee Effectiveness, Corporate Social Responsibility, company size. and variables that do not have a significant effect are institutional stock ownership and the Debt To Equity Ratio. positively and significantly. Individual companies are affected by profitability; The biggest positive influence is the company Japfa Comfeed Indonesia Tbk, the smallest positive is the Lion Metal Work Tbk company, and the biggest negative influence is the Bata Shoe Company Tbk, the smallest negative is the company Holcim Indonesia Tbk. The results of this study have implications for firm value (Tobins Q); The variables that show a positive and significant influence are the variable of Audit Committee Effectiveness, Corporate Social Responsibility, Company Size, and Debt To Equity Ratio, Return on Asset variables that have no effect are Institutional Share Ownership, Managerial Share Ownership. the biggest positive influence on changes (Tobins Q) of the company Japfa Comfeed Indonesia Tbk. the smallest positive is the company Semen Batu Raja Tbk, the biggest negative influence is the Company Tempo Scan Pacific Tbk; The smallest negative influence is the company Holcim Indonesia Tbk.